Do Dose-Dependent Microbial Changes Occur during Spine Surgery as a Result of Applying Intrawound Vancomycin Powder?: A Systematic Literature Review - Lunli Xie; Jun Zhu; Shunhong Luo; Yu Xie; Dan Pu (Asian Spine Journal, 2018)
We analyzed dose-dependent effects of vancomycin on wound infection bacteria and investigated the relationship between dose and microbial imbalances in patients treated with intrawound vancomycin powder during spine surgery. Numerous trials have confirmed that using intrawound vancomycin powder during spine surgery may decrease postoperative wound infection rates. However, potential risks include changes in wound infection bacteria, inhibition of bone fusion, and systemic toxicity. We searched PubMed for articles published since October 2016 with the following terms: “local vancomycin” or “intrawound vancomycin” or “intraoperative vancomycin” or “intrawound vancomycin” or “topical vancomycin” and “spinal surgery” or “spine surgery.” We also screened the reference lists of included articles for additional studies and extracted data related to dose, infecting bacteria, sample size, infection rate and types, location of spine surgery, and perioperative antibiotics used. Our review includes one prospective and nine retrospective studies. Overall, 1 or 2 g local vancomycin powder was used in 2,394 patients. Gram-negative bacteria were dominant in patients in whom 1 g vancomycin powder was used, whereas gram-positive bacteria were dominant in those in whom 2 g powder was used. The exact mechanism underlying this dose-dependent trend remains unclear, although it may be attributed to the pharmacological characteristics of vancomycin. The included studies showed that trends in infection bacteria may change after the use of topical vancomycin powder. In addition, the observed increase in gram-negative bacteria when intrawound vancomycin powder is used has generated considerable attention. The present results differ from previous results but do not provide additional information regarding vancomycin dose and microbial changes in infected wounds. Additional large randomized controlled trials are needed to determine the relationship between vancomycin dose and the types of wound infection bacteria in patients treated with intrawound vancomycin powder during spine surgery.